Effects of superfine grinding using ball‐milling on the physical properties, chemical composition, and antioxidant properties of Quercus salicina (Blume) leaf powders - Hong, Seong‐Jin; Das, Protiva Rani; Eun, Jong‐Bang (Journal of the science of food and agriculture, 2021)
BACKGROUND Quercus salicina (Blume) leaves are traditionally used as folk medicine in some Asian countries. The aim of this study was to evaluate the effects of ball milling for different periods (0, 6, 12, 18, and 24 h) on the physicochemical properties of superfine Quercus salicina (Blume) leaf (QSL) powders. RESULTS The particle sizes, water‐holding capacity, angle of repose, and redness of the superfine QSL powder decreased with increasing ball‐milling times, whereas the water solubility index, bulk density, tapped density, brightness, and yellowness were found to increase. Significantly higher (P > 0.05) total phenolic and flavonoid contents, and antioxidant activities, were observed for the superfine QSL powders obtained after 24 h ball‐milling time. A total of 12 phenolic compounds in free and cell‐wall‐bound forms were quantified in the superfine QSL powder. Free phenolics such as protocatechuic acid, caffeic acid, rutin, and p‐coumaric acid were increased and all cell‐wall‐bound phenolics were decreased with increasing ball‐milling times. The antioxidant activity of the free phenolics increased with increasing ball‐milling times, and the cell‐wall‐bound forms decreased. CONCLUSION Superfine grinding by ball milling for 24 h can thus be used to produce superfine QSL powder with higher free phenolic metabolite content and antioxidant activity, and improved water solubility index, color, bulk, and tapped densities. This study will be useful for the food / nutraceutical / pharmaceutical industries in the manufacturing of active food ingredients or value‐added products using QSL powders. © 2020 Society of Chemical Industry